Concerning the possibility of acceptance legal entity as a subject of a criminal mismanagement using of land - Шульга, А. М.; Цвіркун, Н. Ю. (Theory and practice of jurisprudence, 2016)
This article is devoted to the problem of recognizing a criminal entity, which is caused by the negative impact on the earth and the environment in general by the entities. These two opposing points of view about this issue and the estimation of each of the arguments "for" or "against". The idea to introduce criminal liability of legal persons is promising because it could serve as some incentive to deal effectively with entities that violate the duty to protect land and its socially dangerous activities leading to the onset of negative consequences